Phosphorylated micron zero-valent iron reinforced by liquid nitrogen freezing treatment as well as preparation method and application of phosphorylated micron zero-valent iron
By phosphorylation modification and liquid nitrogen freezing treatment, phosphorylated micron zero-valent iron enhanced by liquid nitrogen freezing treatment is formed, which solves the problem of removing heavy metal complexes in mining wastewater and achieves efficient effect of synchronous removal of heavy metal ions and organic ligands.
Patent Information
- Application Number
- CN202411916817.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The prior art is difficult to effectively remove heavy metal complexes in mining wastewater, and traditional methods cannot simultaneously remove heavy metal ions and organic ligands, resulting in serious environmental and health hazards.
By undergoing phosphorylation modification and liquid nitrogen freezing treatment, phosphorylated micron zero-valent iron (P-ZVIbm&ln) enhanced by liquid nitrogen freezing treatment, this material can activate dissolved oxygen, produce reactive oxygen species, oxidize and degrade organic agents, and remove heavy metal ions through reduction fixation.
It has achieved efficient removal of heavy metal-organic smelting agent complexes, effectively mineralized organic ligands, reduced the ecological toxicity of wastewater, and the material preparation process is simple, low cost, and has good cycle reaction stability.
Smart Images

Figure CN119733825A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy metal-organic dressing agent complex pollution control, and specifically relates to liquid nitrogen freezing treatment-enhanced phosphated micron zero-valent iron and a preparation method and application thereof. Background Art
[0002] The rapid development of mining will generate a large amount of mining wastewater, which may contain harmful heavy metal ions (such as Cu 2+ The heavy metal ions with empty orbitals as Lewis acids are easy to coordinate with organic agents with lone pairs of electrons that can act as Lewis bases to form heavy metal complexes. The residual organic agents contained in mine wastewater will cause organic pollution to the environment if they are directly discharged without treatment. Moreover, heavy metal complexes have higher stability and mobility, so they are more harmful to the environment and health. In addition, if mine wastewater is directly reused without treatment, it will seriously affect the mineral processing effect. At the same time, heavy metal complexes are difficult to be effectively removed by traditional methods (such as adsorption and precipitation), so there is an urgent need to develop efficient methods for removing heavy metal complexes.
[0003] The treatment of heavy metal complex pollution requires the simultaneous removal of heavy metal ions and degradation of organic ligands. Simple decomplexation cannot remove organic ligands and requires additional steps to remove heavy metal ions. Simple oxidative degradation can only remove organic ligands. Therefore, it is urgent to develop an effective method that can simultaneously remove heavy metal ions and degrade organic ligands. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a liquid nitrogen freezing treatment-enhanced phosphorylated micron zero-valent iron (P-ZVI bm&ln ) and its preparation method and application.
[0005] Zero-valent iron (ZVI) has the advantages of being environmentally friendly, cost-effective, and highly reactive, and has received widespread attention in the field of environmental pollution control. However, the surface of zero-valent iron is prone to form a (hydr)oxide passivation layer, which will hinder the release and transfer of its electrons, thereby greatly reducing the reactivity of zero-valent iron. By modifying zero-valent iron, it is expected to break the active barrier of its passivation layer, making it possible to use it for one-stop removal of heavy metals and organic agent ligands complexed with it in mine wastewater. An important strategy for zero-valent iron modification is to increase the surface ferrous (≡Fe 2+ ) active sites, which can then activate hydrogen peroxide (H2O2), dissolved oxygen (O2), persulfate (PS), sodium chlorite (NaClO2), etc., to produce hydroxyl radicals (·OH), singlet oxygen ( 1 O2), sulfate radical (SO4 ·- ), high-valent iron (FeV / Fe IV ) and other active species to oxidize and degrade organic pollutants. Dissolved oxygen can be activated as a green oxidant to produce reactive oxygen species (ROS) to oxidatively degrade organic ligands, and no additional oxidants need to be added, which can reduce costs. In addition, the removal of heavy metal ions by zero-valent iron mainly depends on the reduction and fixation of heavy metal ions by elemental iron, so the modification of zero-valent iron is very important in improving the surface ferrous iron (≡Fe 2+ ) active sites, while also exposing more internal iron cores (Fe 0 ), thereby improving its removal performance for heavy metal ions.
[0006] The ferrous phosphate shell formed by phosphorylation of zero-valent iron has more surface ferrous iron (≡Fe 2+ ) active sites, which will significantly promote the activation of dissolved oxygen and the generation of reactive oxygen species (ROS), and then efficiently oxidatively degrade and even oxidize and mineralize organic agents (heavy metal complexing ligands). The significance of liquid nitrogen freezing treatment is that cracks can be formed on the phosphorylated micron zero-valent iron, thereby exposing more internal zero-valent iron cores (Fe 0 ), which will significantly enhance its reduction and fixation of heavy metal ions. At the same time, more exposed elemental iron is easy to react with the trivalent iron ions dissolved by the activated dissolved oxygen (Fe 0 +2Fe 3+ →3Fe 2+ ) to regenerate the surface ferrous iron, breaking through the bottleneck of ferrous iron regeneration through efficient iron circulation, thereby greatly improving the recycling reaction capacity. Phosphorylation modification and liquid nitrogen freezing treatment expose more surface ferrous iron (≡Fe 2+ ) and elemental iron (Fe 0 ), significantly improving the liquid nitrogen freezing treatment-enhanced phosphorylated micronized zero-valent iron (P-ZVI bm&ln ) to remove the comprehensive performance of typical heavy metal-organic dressing agent complex (benzohydroxamic acid complexed copper, Cu(II)-BHA) and actual mine wastewater (containing organic agents and heavy metals).
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing liquid nitrogen freezing-treated and enhanced phosphorylated micron zero-valent iron comprises the following steps:
[0009] Micron zero-valent iron powder and a phosphate precursor are mixed and ball-milled by a mechanochemical method to obtain phosphated micron zero-valent iron, and the phosphated micron zero-valent iron is cryogenically frozen with liquid nitrogen to obtain phosphated micron zero-valent iron strengthened by liquid nitrogen freezing treatment.
[0010] Preferably, the phosphorylation precursor includes at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, phosphoric acid, sodium monohydrogen phosphate, potassium monohydrogen phosphate, sodium phosphate, and potassium phosphate;
[0011] Preferably, the molar ratio of the phosphorylated precursor to the micron zero-valent iron powder (measured in molar amount of iron element) is 0.01 to 0.1:1 (0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1);
[0012] Further preferably, the optimal molar ratio of the phosphorylated precursor to the micron zero-valent iron powder is 0.07:1.
[0013] Preferably, the particle size of the micron zero-valent iron powder is 80-300 μm.
[0014] Further preferably, the particle size of the micron zero-valent iron powder is 60-120 μm.
[0015] Preferably, the micron zero-valent iron powder is industrial iron powder. Industrial iron powder has low cost (about 12 yuan / kg), and its main components include elemental iron and iron (hydroxide).
[0016] Preferably, the ball milling is mechanical ball milling;
[0017] Preferably, the diameters of the stainless steel milling beads used in the ball mill are 0.4-0.6 cm and 1.0-1.2 cm.
[0018] Further preferably, the diameters of the stainless steel milling beads used in the ball milling are 0.6 cm and 1.0 cm.
[0019] Preferably, the ball mill speed of the ball mill is 400-800 rpm, and the ball milling time is 1-5 hours.
[0020] Further preferably, the ball mill speed of the ball mill is 500 rpm, and the ball milling time is 4 hours.
[0021] Preferably, the low-temperature freezing is liquid nitrogen immersion;
[0022] Preferably, the low-temperature freezing time is 10 to 15 minutes.
[0023] More preferably, the low-temperature freezing time is 10 minutes.
[0024] The above-mentioned preparation method prepares phosphated micron zero-valent iron strengthened by liquid nitrogen freezing treatment.
[0025] The above-mentioned liquid nitrogen freezing treatment-enhanced phosphated micron zero-valent iron is used in the treatment of wastewater containing heavy metals and / or organic matter. It can activate dissolved oxygen to produce reactive oxygen species (ROS) to oxidatively degrade and even mineralize organic agents (complexing ligands), while efficiently removing heavy metal ions and having good cyclic reaction stability.
[0026] Preferably, the wastewater containing heavy metals and / or organic matter is wastewater containing heavy metal complexes.
[0027] More preferably, the heavy metal complex is copper benzohydroxamic acid complex (Cu(II)-BHA).
[0028] Preferably, the wastewater containing heavy metals and / or organic matter is actual mine wastewater containing organic agents and heavy metals.
[0029] Preferably, the treatment of wastewater containing heavy metals and / or organic matter is carried out on a shaker at 220 rpm, with a reaction time of 1 h.
[0030] Preferably, the concentration of benzohydroxamic acid complex copper (Cu(II)-BHA) for removing heavy metal complex pollutants in simulated mine wastewater is 0.2 mmol / L, no external reagent is added to adjust the pH, and no additional oxidant and precipitant are added.
[0031] A method for treating wastewater contaminated by heavy metal complexes in simulated mine wastewater comprises the following steps:
[0032] 0.5 g of the above liquid nitrogen freezing treatment-enhanced phosphorylated micronized zero-valent iron (P-ZVI bm&ln ) was added to 100 mL of benzohydroxamic acid complexed copper (Cu(II)-BHA) for batch treatment experiments.
[0033] The beneficial effects of the present invention are:
[0034] The liquid nitrogen freezing treatment-enhanced phosphorylated micron zero-valent iron (P-ZVI bm&ln ) can remove benzohydroxamic acid complexed copper, a typical heavy metal-organic dressing agent complex, in one stop. It can effectively mineralize organic ligands and remove heavy metal ions efficiently, with high reaction efficiency and strong cyclic reactivity. bm&ln It can efficiently treat actual mine wastewater containing organic agents and heavy metals. The treatment results meet national emission standards and significantly reduce the ecological toxicity of the wastewater. The material preparation process is simple, the production cost is low, and it is environmentally friendly. It has a very broad application prospect in the field of heavy metal complex pollution control in mine wastewater.
[0035] Specifically:
[0036] 1) The liquid nitrogen freezing treatment-enhanced phosphated micronized zero-valent iron in the present invention has a ferrous phosphate layer formed during the phosphate process, which makes it have rich surface ferrous iron (≡Fe 2+ ) active sites, greatly improving its activation ability for dissolved oxygen and the production of reactive oxygen species (ROS), thereby enhancing its performance in oxidative degradation of organic agents, effectively mineralizing and removing complexing ligands, and avoiding the risk of complexation.
[0037] 2) The phosphorylation modification of zero-valent iron in the present invention can significantly increase the surface ferrous iron (≡Fe 2+ ) active site content, and the phosphate ions (PO4 3- ) can assist in the removal of heavy metal ions through adsorption and precipitation.
[0038] 3) In the process of the present invention of subjecting the phosphated zero-valent iron to liquid nitrogen freezing treatment, the low-temperature freezing by immersion in liquid nitrogen can cause the surface of the phosphated zero-valent iron to crack and form cracks, thereby exposing more of the internal iron core (Fe 0 ), which will significantly enhance its reduction and fixation of heavy metal ions. At the same time, more exposed elemental iron is easy to react with the trivalent iron ions dissolved by the activated dissolved oxygen (Fe 0 +2Fe 3+ →3Fe 2+ ), which regenerates ferrous iron through an efficient iron cycle, thereby greatly improving the cycle reactivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a mechanism diagram of the treatment of benzohydroxamic acid complexed copper by phosphorylated micronized zero-valent iron enhanced by liquid nitrogen freezing treatment of the present invention.
[0040] Figure 2 X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA&DTG) of the ball-milled micron zero-valent iron, liquid nitrogen-frozen ball-milled micron zero-valent iron, phosphated ball-milled micron zero-valent iron and liquid nitrogen-frozen phosphated ball-milled micron zero-valent iron of Examples 1 to 4 were analyzed.
[0041] Figure 3 The Mössbauer analysis of the liquid nitrogen-frozen ball-milled micronized zero-valent iron and the liquid nitrogen-frozen phosphated ball-milled micronized zero-valent iron of Examples 3 and 4 is shown in FIG. Spectral analysis.
[0042] Figure 4 Selected area electron diffraction (SAED), high resolution transmission electron microscopy and energy dispersive spectroscopy (HR-TEM&EDS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) analysis of the phosphated micron zero-valent iron strengthened by liquid nitrogen freezing treatment of Example 4.
[0043] Figure 5Atomic force microscopy (AFM) and potential analysis of the phosphated micronized zero-valent iron strengthened by liquid nitrogen freezing treatment in Example 4.
[0044] Figure 6 High resolution X-ray photoelectron spectroscopy (HR-XPS) analysis of the ball-milled micron zero-valent iron, phosphated ball-milled micron zero-valent iron and phosphated ball-milled micron zero-valent iron enhanced by liquid nitrogen freezing treatment of Examples 1, 3 and 4.
[0045] Figure 7 Density functional theory (DFT) calculation analysis of zero-valent iron and phosphorylated zero-valent iron before and after phosphoric acid modification and their potential to activate molecular oxygen in Examples 1 to 4.
[0046] Figure 8 The diagram shows the effects of treating benzohydroxamic acid-complexed copper with ball-milled micron zero-valent iron, liquid nitrogen-frozen ball-milled micron zero-valent iron, phosphated ball-milled micron zero-valent iron, and liquid nitrogen-frozen phosphated ball-milled micron zero-valent iron of Examples 1 to 4.
[0047] Fig. 9 This is a diagram showing the effect of treating benzohydroxamic acid-complexed copper with ball-milled micronized zero-valent iron treated with liquid nitrogen and frozen with ferrous phosphate, ferric phosphate, sodium dihydrogen phosphate or ferrous sulfate heptahydrate.
[0048] Fig.10 This is a diagram showing the effect of continuously cyclically treating benzohydroxamic acid-complexed copper with ball-milled micron zero-valent iron, liquid nitrogen-frozen ball-milled micron zero-valent iron, phosphated ball-milled micron zero-valent iron, and liquid nitrogen-frozen phosphated ball-milled micron zero-valent iron of Examples 1 to 4.
[0049] Fig.11 This is a diagram showing the effect of treating actual wastewater with liquid nitrogen-frozen phosphorylated ball-milled micron zero-valent iron in Example 4.
[0050] Fig.12 This is a diagram showing the effect of treating benzohydroxamic acid-complexed copper with liquid nitrogen-frozen phosphorylated ball-milled micron zero-valent iron of Examples 5 to 6. DETAILED DESCRIPTION
[0051] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0052] The industrial zero-valent iron powder used in the following examples has a particle size of 60 to 120 μm.
[0053] Embodiment 1:
[0054] A ball-milled micronized zero-valent iron, the preparation method of which is as follows:
[0055] 20 stainless steel ball milling beads with a diameter of 1 cm and 50 stainless steel ball milling beads with a diameter of 0.6 cm were added to a stainless steel ball milling jar, purged with argon (Ar) for 3 minutes, and then 5.0 g of industrial zero-valent iron powder was added and mixed evenly. The ball milling jar was then placed in a planetary ball mill, and the speed of the ball mill was adjusted to 500 rpm and run for 4 hours (the running direction was changed every hour), and the ball-milled micron zero-valent iron (denoted as ZVI) was obtained. bm ).
[0056] Embodiment 2:
[0057] A phosphorylated micronized zero-valent iron, the preparation method of which is as follows:
[0058] 20 stainless steel ball milling beads with a diameter of 1 cm and 50 stainless steel ball milling beads with a diameter of 0.6 cm were added to a stainless steel ball milling jar, purged with argon (Ar) for 3 min, and then 5.0 g of industrial zero-valent iron powder and 0.75 g of sodium dihydrogen phosphate (NaH2PO4) were added and mixed evenly (the molar ratio of sodium dihydrogen phosphate to iron was 0.07:1). Then, the ball milling jar was placed in a planetary ball mill, and the speed of the ball mill was adjusted to 500 rpm. The mill was run for 4 h (the running direction was changed every hour), and phosphorylated micron zero-valent iron (denoted as P-ZVI) was obtained. bm ).
[0059] Embodiment 3:
[0060] A liquid nitrogen-freezing ball-milled micronized zero-valent iron, the preparation method of which is as follows:
[0061] 20 stainless steel ball milling beads with a diameter of 1 cm and 50 stainless steel ball milling beads with a diameter of 0.6 cm were added to a stainless steel ball milling jar, purged with argon (Ar) for 3 minutes, and then 5.0 g of industrial zero-valent iron powder was added and mixed evenly. The ball milling jar was then placed in a planetary ball mill, and the speed of the ball mill was adjusted to 500 rpm and run for 4 hours (the running direction was changed every hour), and ball-milled micron zero-valent iron was obtained;
[0062] After the ball milling beads were taken out from the ball milling jar, liquid nitrogen was added to the ball milling jar and the jar was immersed and frozen for 10 minutes to obtain the ball milled micron zero-valent iron (denoted as ZVI) frozen by liquid nitrogen. bm&ln ).
[0063] Embodiment 4:
[0064] A liquid nitrogen freezing-treated and strengthened phosphated micronized zero-valent iron, the preparation method of which is as follows:
[0065] 20 stainless steel ball milling beads with a diameter of 1 cm and 50 stainless steel ball milling beads with a diameter of 0.6 cm were added to a stainless steel ball milling jar, purged with argon (Ar) for 3 minutes, and then 5.0 g of industrial zero-valent iron powder and 0.75 g of sodium dihydrogen phosphate (NaH2PO4) were added and mixed evenly (the molar ratio of sodium dihydrogen phosphate to iron was 0.07:1). Then, the ball milling jar was placed in a planetary ball mill, and the speed of the ball mill was adjusted to 500 rpm and run for 4 hours (the running direction was changed every hour), thereby obtaining phosphorylated micron zero-valent iron;
[0066] After the ball mill beads were taken out from the ball mill, liquid nitrogen was added to the ball mill and the mixture was immersed in the liquid nitrogen freezing treatment for 10 min to obtain phosphorylated micronized zero-valent iron (denoted as P-ZVI). bm&ln ).
[0067] Phosphorylated micron zero-valent iron (P-ZVI) strengthened by liquid nitrogen freezing treatment of the present invention bm&ln ) treatment mechanism of copper(II)-BHA Figure 1 shown.
[0068] ZVI in Examples 1 to 4 bm , ZVI bm&ln 、P-ZVI bm and P-ZVI bm&ln A series of characterizations and density functional theory (DFT) calculations and analyses of Figures 2 to 7 shown.
[0069] Depend on Figure 2 From (a) in the figure, we can see that: ZVI bm , ZVI bm&ln 、P-ZVI bm and P-ZVI bm&ln The XRD peaks of the product are consistent with the standard XRD spectrum card of iron (Fe 06-0696), indicating that ball milling phosphorylation modification and liquid nitrogen freezing treatment did not change the main crystal form of zero-valent iron, and its main crystal form is still zero-valent iron. Figure 2 (b) P-ZVI bm&ln The FT-IR analysis results show that the -1 The infrared peaks at 555.5 and 1384.8 cm-1 are consistent with those of ferrous phosphate and ferric phosphate. -1 The infrared peak at is consistent with ferrous phosphate well, but poorly consistent with ferric phosphate, indicating that ferrous phosphate may be generated during the phosphorylation modification of zero-valent iron. In addition, the infrared spectrum results calculated by DFT are consistent with the strongest infrared peak of the measured results, which verifies the reliability of the model used in subsequent DFT calculations. Figure 2 (c) P-ZVI bm&lnThermogravimetric analysis and differential analysis of ferrous phosphate show that: P-ZVI bm&ln The thermogravimetric analysis curve of P-ZVI is consistent with that of ferrous phosphate. bm&ln May contain ferrous phosphate.
[0070] Depend on Figure 3 (a) ZVI bm&ln of Spectral analysis shows that: ZVI bm&ln The main components and their proportions are elemental iron (89.7%), basic iron oxide (7.9%) and ferrous oxide (2.4%). Figure 3 (b) P-ZVI bm &ln of Spectral analysis shows that: P-ZVI bm&ln The main components and their proportions are elemental iron (90.7%), ferrous phosphate (6.6%) and ferric phosphate (2.7%), which verifies the ferrous phosphate generated by the phosphate modification process.
[0071] Depend on Figure 4 (a) P-ZVI bm&ln The SAED analysis shows that the diffraction patterns of (2 0 0), (001) and (2 1 1) belonging to iron and the diffraction patterns of (3 1 0) and (0 0 1) belonging to ferrous phosphate can be analyzed, indicating that ferrous phosphate is generated after phosphorylation modification of zero-valent iron. Figure 4 (b) P-ZVI bm&ln The TEM&EDS analysis results show that P-ZVI bm&ln It has a shell rich in phosphorus, with a thickness of about 50 to 100 nm. Figure 4 (c) P-ZVI bm&ln ToF-SIMS and 3D depth analysis tests show that the thickness of its ferrous phosphate shell is about 50nm.
[0072] Depend on Figure 5 Medium P-ZVI bm&ln AFM and potential analysis tests show that after liquid nitrogen freezing treatment, cracks with a width of about 173.2 to 463.1 nm and a depth of about 72.0 to 81.2 nm are formed, which may expose more internal zero-valent iron cores (Fe 0 ). At the same time, the potential analysis results show that the potential deep in the crack is lower than that on the surface, which is conducive to the migration of electrons from the inside to the surface.
[0073] Depend on Figure 6 (a) ZVI bm and (b) P-ZVI bm and (c) P-ZVIbm&ln HR-XPS (Fe 2p) analysis showed that phosphorylation modification significantly increased the content of surface ferrous iron, and liquid nitrogen freezing treatment significantly increased the content of surface elemental iron.
[0074] Depend on Figure 7 (a) Density functional theory (DFT) calculation analysis of zero-valent iron before and after phosphate modification shows that the phosphate modification significantly reduces the O2 adsorption energy, which will promote the adsorption of dissolved oxygen. At the same time, Mulliken and Hirshfeld charge analysis shows that the O2 adsorbed by P-ZVI has more charge and will be more easily activated. Bond length analysis found that the OO bond length of O2 in the P-ZVI system is Longer than the bond length of O2 in ZVI system It shows that its antibonding molecular orbital (π * 2p ) may have more electrons filling and generate O2 ·- or O2 2- , verifying the activation of O2 in the P-ZVI system. Phosphorylation modification increases the highest occupied molecular orbital (HOMO) energy level of P-ZVI, which will be beneficial to the release of electrons, while the band gap (E LUMO -E HOMO ) will promote the migration of electrons, and the reduction of P-ZVI work function will promote its contribution of electrons. Figure 7 Comparison of the differential charge density analysis between (b) and (c) shows that phosphorylation modification promotes electron transfer between P-ZVI and O2, which will be beneficial to the activation of dissolved oxygen and the generation of reactive oxygen species (ROS).
[0075] Further testing of material properties: 0.5 g of ZVI from Examples 1 to 4 was added bm , ZVI bm&ln 、P-ZVI bm and P-ZVI bm&lnThey were added to 100 mL of 0.2 mmol / L benzohydroxamic acid complex copper (Cu(II)-BHA) solution, and then placed in a shaker at 220 rpm for 1 h. Samples were taken at 15, 30, 45 and 60 min and filtered with a 0.22 μm filter for analysis. The removal of heavy metal complexes requires the simultaneous capture of heavy metals and degradation of organic ligands. If only the organic ligands are destroyed without deep oxidation degradation, the degraded organic intermediates will remain, and their potential toxicity may still cause environmental pollution hazards, and there is also a risk of complexation. Therefore, the goal of this study is to achieve full oxidation degradation and even mineralization of organic flotation agents (organic ligands) and simultaneous removal of heavy metals. The total organic carbon (TOC) analyzer can be used to determine the removal rate of TOC, which can effectively reflect the degree of oxidation degradation of organic ligands in the heavy metal complex system, thereby evaluating the degradation effect of the organic agent BHA. At the same time, the residual concentration of heavy metal total copper was determined by atomic absorption spectrometry (AAS). Both methods have been verified to show excellent linearity.
[0076] Removal effect Figure 8 As shown in (a) and (b): ZVI bm and ZVI bm&ln The TOC removal rate of the system was less than 1.5%, and the organic ligands in Cu(II)-BHA were almost incapable of degradation. The total Cu could be removed by ca.89.0% and 90.1%, respectively. bm ) system significantly reduced TOC, degraded ca.79.5% of BHA and removed ca.90.0% of total Cu. Phosphated micronized zero-valent iron (P-ZVI) enhanced by liquid nitrogen freezing treatment bm&ln ) system significantly reduced the TOC in Cu(II)-BHA, degrading ca.85.3% of the organic ligands and removing ca.100% of the total copper. Figure 8 From (a) and (b) in Figure 2, we can see that zero-valent iron phosphorylation significantly improved the performance of degrading organic agent ligands, while liquid nitrogen freezing treatment significantly improved the ability to remove heavy metal ions. bm&ln It has excellent removal effect of copper benzohydroxamic acid complex (Cu(II)-BHA), and achieves simultaneous degradation of organic agent ligands and removal of heavy metal ions.
[0077] in addition, Fig. 9 In ZVI bm&lnFerrous phosphate (0.223 g, n(P):n(ZVI)=7%) or ferric phosphate (0.094 g, n(P):n(ZVI)=7%) and sodium dihydrogen phosphate (0.075 g, n(P):n(ZVI)=7%) or ferrous sulfate heptahydrate (0.0025 g, C(Fe 2+ )=5mg / L) and then reacted with Cu(II)-BHA. The experimental results show that ZVI bm&ln The addition of ferrous phosphate or ferric phosphate and sodium dihydrogen phosphate or ferrous sulfate heptahydrate to the system can only increase the removal rate of organic agent ligands by ca.13.5% and ca.1.8% and ca.10.5% and ca.7.9%, respectively. The above results show that P-ZVI bm&ln The ability of activated dissolved oxygen to generate ROS to oxidatively degrade organic ligands is enhanced by the surface ferrous iron (≡Fe 2+ ) active site.
[0078] Depend on Fig.10 From (a) and (b) in the figure, we can see that in the continuous cycle reaction, ZVI bm and ZVI bm&ln The organic reagent ligands in Cu(II)-BHA can hardly be removed. bm and P-ZVI bm&ln It showed good ability to remove Cu(II)-BHA in a cycle. bm and P-ZVI bm&ln The organic ligands can be degraded by ca. 60.1% and 80.0% respectively, the third cycle removal reaction can degrade ca. 40.0% and 70.1% respectively, and the fourth cycle removal reaction can degrade ca. 24.9 and 61.1% respectively. P-ZVI bm&ln The ability of continuous cyclic reaction to degrade organic ligands in Cu(II)-BHA was significantly improved, and the performance of continuous cyclic removal of total Cu was also improved. The total copper cyclic removal rate was maintained above 97.7%, which has good application potential.
[0079] Depend on Fig.11 From (a) and (b) in Figure 1, we can see that using P-ZVI bm&lnActual wastewater from a copper mine in East China and Southwest China (ore dressing wastewater containing residual organic reagents and acid mine drainage containing heavy metals) was treated. The initial chemical oxygen demand (COD) concentrations were ca.213.2mg / L and 545.2mg / L, the initial total organic carbon (TOC) concentrations were ca.14.5mg / L and 12.8mg / L, and the initial total Cu concentrations were ca.16.9mg / L and 40.1mg / L, respectively. The batch reaction volume was 100mL, and P-ZVI bm&ln The dosage was 5 g / L, the batch reaction time was 1 h, and the continuous cycle reaction was repeated 3 times. In the actual wastewater treatment results of a copper mine in East China, the first two continuous treatments could remove ca.54.4% and 53.1% of COD, ca.70.2% and 68.3% of TOC, ca.99.1% and 98.4% of total Cu, respectively, with average removal rates of 114.5, 10.1, and 16.7 mg·L -1 ·h -1 In the actual wastewater treatment results of a copper mine in the southwest region, the first two consecutive treatments can remove ca.83.3% and 81.8% of COD, ca.60.2% and 58.7% of TOC, ca.99.5% and 98.9% of total Cu, and the average removal rates are 449.9, 7.6, and 39.8 mg·L, respectively. -1 ·h -1 The COD and total Cu concentrations in the first two continuous treatment results of the two actual mine wastewaters can reach the farmland irrigation water quality standard of the People's Republic of China GB 5084-2021 (COD ≤ 150 mg / L, total Cu ≤ 0.5 mg / L) and the copper, nickel and cobalt industrial pollutant emission standard GB 25467-2010 (COD ≤ 100 mg / L, total Cu ≤ 0.5 mg / L). The cyclic reactivity is strong and has good practical application prospects.
[0080] In addition, in order to explore the changes in the ecological toxicity of actual mine wastewater, actual wastewater from a copper mine in East China and Southwest China was used to cultivate mung bean seeds. The germination rate of mung bean seeds cultivated with untreated copper mine wastewater in East China was 18.8%, and the germination rate of mung bean seeds cultivated with P-ZVI was 18.8%. bm&ln The treated wastewater increased the germination rate to 87.5%. The germination rate of mung bean seeds cultivated with untreated copper mine wastewater in the southwest region was 6.3%. bm&ln The treated wastewater increased the germination rate to 81.3%. The above results show that P-ZVI bm&ln The treatment significantly reduced the eco-toxicity of mine wastewater.
[0081] Embodiment 5:
[0082] Phosphorylated micronized zero-valent iron (P-ZVI) was synthesized using sodium dihydrogen phosphate as a phosphorylation precursor with a mol ratio of 1% to 9% liquid nitrogen freezing treatment. bm&ln ) (The only difference from Example 4 is the different amount of sodium dihydrogen phosphate used).
[0083] Embodiment 6:
[0084] P-ZVI synthesized using other phosphorylated precursors (phosphoric acid and sodium monohydrogen phosphate and sodium phosphate) bm&ln (The only difference from Example 4 is the phosphorylated precursor).
[0085] The performance of the materials in Examples 5 and 6 in removing Cu(II)-BHA after reacting for 1 hour was tested using the above-mentioned method for testing material performance.
[0086] Fig.12 (a) is the performance of removing Cu(II)-BHA in Example 5. It is found that P-ZVI with a mol ratio of 7% bm&ln It has the best BHA degradation and total Cu removal performance. Fig.12 (b) shows the performance of removing Cu(II)-BHA in Example 6. The results show that P-ZVI with sodium dihydrogen phosphate as the precursor bm&ln It has the best BHA degradation and total Cu removal performance.
[0087] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, replacements, simplifications, and combinations that do not deviate from the scientific essence and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing phosphorylated micron zero-valent iron strengthened by liquid nitrogen freezing treatment, characterized in that: The following steps are involved: Micron zero-valent iron powder and a phosphate precursor are mixed and ball-milled by a mechanochemical method to obtain phosphated micron zero-valent iron, and the phosphated micron zero-valent iron is cryogenically frozen with liquid nitrogen to obtain phosphated micron zero-valent iron strengthened by liquid nitrogen freezing treatment.
2. The preparation method according to claim 1, characterized in that: The phosphorylation precursor includes at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate, phosphoric acid, sodium monohydrogen phosphate, potassium monohydrogen phosphate, sodium phosphate, and potassium phosphate; The molar ratio of the phosphorylated precursor to the micronized zero-valent iron powder is 0.01 to 0.1:1; The particle size of the micron zero-valent iron powder is 80-300 μm.
3. The preparation method according to claim 1, characterized in that: The ball milling is mechanical ball milling; The diameters of the stainless steel ball milling beads used in the ball milling are 0.4-0.6 cm and 1.0-1.2 cm.
4. The preparation method according to claim 1, characterized in that: The ball mill rotation speed of the ball mill is 400-800 rpm, and the ball milling time is 1-5 hours.
5. The preparation method according to claim 1, characterized in that: The low temperature freezing is liquid nitrogen immersion; The low-temperature freezing time is 10 to 15 minutes.
6. Phosphorylated micronized zero-valent iron strengthened by liquid nitrogen freezing treatment prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the phosphated micronized zero-valent iron strengthened by liquid nitrogen freezing treatment as claimed in claim 6 in treating wastewater containing heavy metals and / or organic matter.
8. The use according to claim 7, characterized in that: The wastewater containing heavy metals and / or organic matter is wastewater containing heavy metal complexes.
9. The use according to claim 8, characterized in that: The heavy metal complex is benzohydroxamic acid complexed copper.
10. The use according to claim 7, characterized in that: The wastewater containing heavy metals and / or organic matter is actual mine wastewater containing organic agents and heavy metals.
Citation Information
Patent Citations
Method for treating commercial iron powder by liquid oxygen at low temperature for enhancing pollutant reductive removal ability
CN107188291A
Phosphorus-doped zero-valent iron modified material, preparation method thereof and method for efficiently reducing and removing pollutants by using phosphorus-doped zero-valent iron modified material
CN115784412A
Phosphating modified zero-valent iron material as well as preparation method and application thereof
CN116550972A
Method for preparing sulfur-nitrogen modified zero-valent iron through wet ball milling, sulfur-nitrogen modified zero-valent iron and application of sulfur-nitrogen modified zero-valent iron
CN118595433A
Preparation method of graphitizable nitrogen complexed Fe(III)-Fe(0) catalyst
JP6843414B1